Air quality inside an underground road tunnel system - Lin, Jiang Xun. (2010)
This study is based on 3 days of constant air quality monitoring with the use of 2 self improvised monitoring devices. The purpose of the study is to draw comparison from the sensors in a latest constructed road tunnel with the measured data from the monitoring devices to ensure the accuracy of the ventilation system sensors.